2015
DOI: 10.1517/13543784.2015.1035708
|View full text |Cite
|
Sign up to set email alerts
|

Kallikrein-related peptidases targeted therapies in prostate cancer: perspectives and challenges

Abstract: Targeting KLK expression and/or activity could be a promising direction in prostate cancer treatment. Future human clinical trials will help us to evaluate the real benefits, toxicities and the consequent optimal use of KLK-targeted drugs, as mono-therapy or in combination regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 94 publications
0
6
0
Order By: Relevance
“…Similarly, a KLK13 specific mAb inhibited the activity of this kallikrein, suggesting that it might have therapeutic application in the treatment of ovarian cancer patients [30]. The overall stability, good tolerance, and long-term inhibitory activity encourage further investigations into the development of specific antibodies as potential therapeutic agents in the treatment of pathologies related to excessive kallikrein activity [31]. …”
Section: Kallikreins As Proteases: Basic Informationmentioning
confidence: 99%
“…Similarly, a KLK13 specific mAb inhibited the activity of this kallikrein, suggesting that it might have therapeutic application in the treatment of ovarian cancer patients [30]. The overall stability, good tolerance, and long-term inhibitory activity encourage further investigations into the development of specific antibodies as potential therapeutic agents in the treatment of pathologies related to excessive kallikrein activity [31]. …”
Section: Kallikreins As Proteases: Basic Informationmentioning
confidence: 99%
“…It was previously reported that kininogen 1, the human homolog, is elevated in the urine of men diagnosed with PCa [ 21 ]. This protein can activate the mitogen-activated protein kinase (MAPK) pathway and promote the proliferation and survival of PCa cells [ 30 ]. EGF is also involved in the regulation of prostate growth and function, and its expression is increased in early and localized PCa; however, in our study, we observed a decrease in its levels in the urine of PCa2 animals and in animals with score 2 lesions, which may be explained by the stage of prostate carcinogenesis [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on our findings, we anticipate that direct/indirect targeting of KLK by selective synthetic KLK inhibitors and modulators will be an effective therapeutic strategy that can be combined with standard chemo-radiotherapy [ 38 ] or immune checkpoint inhibitors, which is especially promising considering the important role of KLKs in the immune response. As in the case of prostate-specific membrane antigen targeted by antitumor vaccines [ 39 ], KLK serine proteases are potential targets for immunotherapy.…”
Section: Discussionmentioning
confidence: 99%